A critical appraisal of the morphological criteria for diagnosing intestinal neuronal dysplasia type B - Terra, Simone A. [UNESP]; De Arruda Lourenção, Pedro L. [UNESP]; Silva, Márcia G. [UNESP]; Miot, Hélio A. [UNESP]; Rodrigues, Maria A.M. [UNESP] (My University, 2017)
Intestinal neuronal dysplasia type B is a controversial entity expressed by complex changes in the enteric nervous system. Diagnosis depends on rectal biopsy histopathology and diagnostic criteria, both qualitative and quantitative, have changed over time, hindering the diagnostic practice. We analyzed the morphological criteria for the histological diagnosis of intestinal neuronal dysplasia type B in a series of patients with intestinal neuronal dysplasia type B according to the 1990 Frankfurt Consensus criteria and verified the applicability of the numerical criteria proposed by Meier-Ruge et al in 2004 and 2006. Qualitative criteria adopted for the histological diagnosis of intestinal neuronal dysplasia type B included hyperplasia of the submucous plexus with hyperganglionosis and hypertrophy of the nerve trunks. Quantitative criteria considered more than 20% giant ganglia in the submucosa, with more than eight neurons each on 25 ganglia, and children aged over 1 year. Distal colon surgical specimens from 29 patients, aged 0-16 years, diagnosed with intestinal neuronal dysplasia type B were retrospectively analyzed using sections processed for conventional histology (H&E) and calretinin immunohistochemistry. Hyperplasia of the submucosal nerve plexi with hyperganglionosis and hypertrophy of the nerve trunks was observed in all cases. Ganglia with small, immature neurons were detected in the majority of cases. Quantitative analysis confirmed hyperganglionosis (mean number=10.7 neurons per ganglion) and hypertrophy of the nerve trunks (median=44.6 μm thickness). Neurons showed immunostaining for calretinin, but neuron counts in calretinin-stained sections were lower compared with H&E (P<0.01). No significant differences were verified between children aged under and over 1 year regarding hyperganglionosis (P=0.79), neuron counts (P=0.36), and immature ganglia (P=0.66). Only one patient met the numerical criteria proposed by Meier-Ruge et al in 2004 and 2006. In conclusion, the numerical criteria showed limited applicability when transposed to conventional histopathology. Children aged over 1 year presented very similar histological features of neuronal immaturity to younger children, questioning the need for an age criterion when diagnosing intestinal neuronal dysplasia type B.